Building interdisciplinary research group for Vocational College Universitas Gadjah Mada - Indah Novita Sari; Ahmad Mu'am (Jurnal Pendidikan Vokasi, 2020)
This research aimed to form a collaborative research and research group in the Department of Languages, Arts and Culture Management, Vocational College of Universitas Gadjah Mada (Departemen Bahasa, Seni, dan Manajemen Budaya or DBSMB). This research is essential for considering DBSMB's needs in developing applied products as a result of interdisciplinary research. On a broader scale, vocational education institutions outside UGM can see an overview of the multidisciplinary research process that has been carried out. The research group was formed in the Culture and Tourism Center, which was based on a functional perspective of organizational functions. The exploratory method was carried out by observation, interview, and literature study. Interviews were conducted with informants consisting of the head of the Teaching Industry Learning Center (TILC), head of study programs, secretary of study programs, and lecturers at DBSMB. The results showed that each lecturer at DBSMB had different research interests. Lecturers' research interests had several intersections that could be made into collaborative research groups. The central theme of culture and tourism could accommodate research collaborations from lecturers in the study programs of Record Management, English, Tourism, Korean Language, and Japanese Language. The challenges in the formation of the research group came from internal factors (communication, funding, and infrastructure) and external factor (collaboration with industry, policy differences, administrative procedures, and interests in research). This research was expected to contribute to the formation of a research group in other vocational education institutions and affect the improvement of vocational graduates' quality and scientific development.